CNS activity of methanol and acetone extracts of Acorus calamus leaves in mice - Pandi, P.V.; Jose, N.; Subhash, H. (2009)
The present study was designed to evaluate CNS depression or analeptic activity of acute oral administration of methanol (ACME) and acetone (ACAE) extracts of Acorus calamus leaves in mice. Spontaneous locomotor activity, immobility time using forced swim test, diazepam-induced sleeping time and motor impairment assessment using rotarod were used to assess CNS depression/analeptic activity of ACME and ACAE in mice. The extracts ACME (5, 20 and 50 mg kg-1, p.o.) and ACAE (20 and 50 mg kg-1, p.o.) significantly decreased the spontaneous locomotor activity in dose dependent manner. The acute treatment of ACME and ACAE (5, 20 and 50 mg kg-1, p.o.) significantly increased the immobility time and decreased the swimming behavior. Administration 6 h prior of ACME (50 mg kg-1, p.o.) and ACAE (20 and 50 mg kg-1, p.o.) significantly potentiated the diazepam (25 mg kg-1, i.p.)-induced sleeping time in mice. These extracts did not induce disturbance in motor coordination. The results of the present research provided evidences that ACME and ACAE may contain psychoactive substances that are CNS depressant in nature. The CNS depression property of these extracts can be utilized for further anticonvulsant research.